Transforming document management for environmental sustainability: the mediating effect of pro-environmental culture and service satisfaction in higher education institutions - Bravo, Jessie; Valdivia, Carlos; Alarcón, Roger; Germán, Nilton; Serquén, Oscar; Aquino, Janet; Arbulú Ballesteros, Marco Agustín; Guevara, Laurita (Frontiers in Sustainability, 2025)
This research investigates the factors influencing environmental sustainability in a Peruvian higher education institution (HEI), using Structural Equation Modeling (SEM) with SmartPLS. The methodology included data collection through questionnaires administered to students, alumni, and professors, followed by SEM analysis to assess the relationships between technological support (TS), document management (DM), open government (OG), pro-environmental organizational culture (POC), service satisfaction (SS), and environmental sustainability (ES). The findings emphasize that technological infrastructure significantly enhances document management, which in turn boosts service satisfaction and promotes a pro-environmental organizational culture. The pro-environmental organizational culture emerges as the most powerful mediator, significantly impacting environmental sustainability. Although service satisfaction also contributes positively, its effect is less pronounced. Furthermore, transparency and open access to information improve document management, albeit with a lesser impact. Sociodemographic variables such as gender and academic program within the institution influence the relationship between the examined variables, suggesting that these characteristics can affect the perception and effectiveness of sustainability practices. This study provides a robust foundation for designing effective strategies to promote environmental sustainability in higher education institutions and would contribute to the fulfillment of the SDGs.